Histopathological Changes during Infected Wound Healing in Cow Calves by the Use of Silver Nano Particle Gel and Povidone Iodine - Singh, Yogendra; Shukla, B.P.; Shukla, Supriya; Jain, Reshma; Jaiswal , Aditya (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was conducted on 12 cow calves with infected wounds, irrespective of sex and breed, divided into two groups having 6 cow calves each. The animals of group I were treated with silver nano particle gel and the animals of group II were treated with povidone iodine dressing for 7 consecutive days. Histopathological changes were recorded at different time interval in both the groups. Studies revealed that there was marked re-epitheliazation and hyperplasia with considerable thickening of epidermis and large amount of collagen deposition in granulation tissue in group I as compared to group II. Histopatathological findings clearly suggest that the group treated with silver nano particle gel showed better and faster healing of wound as compared to povidone iodine treated group. Therefore clinical use of silver nano particle gel can be advocated for wound dressing in cow calves.
Keywords: Histopathological changes; Cow calves; Infected wounds; Silver nano particle (AgNPs); Povidone iodine